2021
DOI: 10.3389/fmolb.2021.710738
|View full text |Cite
|
Sign up to set email alerts
|

RNA Therapeutics - Research and Clinical Advancements

Abstract: RNA therapeutics involve the use of coding RNA such as mRNA as well as non-coding RNAs such as small interfering RNAs (siRNA), antisense oligonucleotides (ASO) to target mRNA, aptamers, ribozymes, and clustered regularly interspaced short palindromic repeats-CRISPR-associated (CRISPR/Cas) endonuclease to target proteins and DNA. Due to their diverse targeting ability and research in RNA modification and delivery systems, RNA-based formulations have emerged as suitable treatment options for many diseases. There… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 136 publications
(150 reference statements)
0
44
0
1
Order By: Relevance
“…The current principle of RNA therapy involves the use of both coding and non-coding RNAs. There are five known types of therapeutic RNAs that are classified by their mode of action: (1) RNAs that inhibit RNA activity (miRNAs, siRNAs, antisense RNAs), (2) RNAs that target proteins (RNA aptamers), (3) RNAs that reprogram genetic information (trans-splicing ribozyme), (4) RNAs that encode therapeutic proteins (mRNAs) and (5) DNA-modifying CRISPR guide RNAs (gRNAs) [ 13 ]. The initial use of RNA as a form of therapy employed chemically synthesised antisense oligonucleotides [ 12 ].…”
Section: Rna Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…The current principle of RNA therapy involves the use of both coding and non-coding RNAs. There are five known types of therapeutic RNAs that are classified by their mode of action: (1) RNAs that inhibit RNA activity (miRNAs, siRNAs, antisense RNAs), (2) RNAs that target proteins (RNA aptamers), (3) RNAs that reprogram genetic information (trans-splicing ribozyme), (4) RNAs that encode therapeutic proteins (mRNAs) and (5) DNA-modifying CRISPR guide RNAs (gRNAs) [ 13 ]. The initial use of RNA as a form of therapy employed chemically synthesised antisense oligonucleotides [ 12 ].…”
Section: Rna Therapymentioning
confidence: 99%
“…These include QPI-1002 and NOX-E36 (Emamticap pegol). QPI-1002 uses an siRNA to target the p53 gene and is currently in phase I and II trials for acute renal failure and AKI, respectively [ 13 ]. NOX-E36 is an RNA aptamer targeting the C-C motif ligand 2, currently in phase II trials for type 2 diabetes mellitus and albuminuria [ 6 , 13 ].…”
Section: Clinical Therapeutic Application Of Rna In Renal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Small interfering RNA (siRNA), as a post transcriptional regulation of gene expression, has been introduced for fundamental treatment of mutant genes in cancer. siRNAs are double-stranded non-coding RNAs generally between 20 and 25 base pairs in length that can interact with the RNA-induced silencing complex (RISC), to degrade and cleave a complementary mRNA ( Feng et al, 2021 ). Although many studies have shown specific gene silencing using siRNA, its delivery in vivo can be challenging due to various biological barriers.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of novel HCC therapeutics have been developed and tested over the last two decades, including molecular targeted therapy, protein antibodies, targeted radionucleotide therapy, and epigenetic therapy. Other HCC therapies include immunotherapy, immune-cell therapy, differentiation strategy and RNA interference (RNAi) ( 2 ). Despite these advances a cure is yet to be developed and to date survival time has only been modestly extended ( 3 ).…”
Section: Introductionmentioning
confidence: 99%